If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 60(10 + -1x) = 90 (10 * 60 + -1x * 60) = 90 (600 + -60x) = 90 Solving 600 + -60x = 90 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-600' to each side of the equation. 600 + -600 + -60x = 90 + -600 Combine like terms: 600 + -600 = 0 0 + -60x = 90 + -600 -60x = 90 + -600 Combine like terms: 90 + -600 = -510 -60x = -510 Divide each side by '-60'. x = 8.5 Simplifying x = 8.5
| 10-3/4x=5 | | -37=-11.9t-4.9t^2 | | 2x-(4x-1)=9 | | x+1+9=3x-24 | | 4.9t^2-125-5.2t=0 | | -2x-13=3x+12 | | 7x+19= | | x+1+9=3-24 | | 5x^4-3x^3-3x^2=0 | | 4-x+2=3x+5 | | 4r-4/8=4r-8/4 | | 46-9x=18+5x | | x/a-5+b | | 6(-7x+3)+2x=1 | | 5y+5.2=2-5y | | (-10*-2)+(2*6)/-2 | | x/3+26=14 | | 5y^2-9x^2-36=0 | | -1=-1.6+-0.8m | | 7*r-7/2 | | x+x+(x+61.5)=180 | | 4(5-3x)= | | -3x=-14+4x | | 8x-52=6x+8 | | -2/3x+53+59 | | 8h+9k-9(8h-9k)= | | 3(2x-5)=6(2+x)+4 | | 21/3x+2=27/3x | | 4x-8y-9x+4y= | | 2(3v+7)=68 | | 1/3(3x-12)=6-2(x-1) | | 18+9/8r=-10 |